2021
DOI: 10.1021/acssuschemeng.1c04498
|View full text |Cite
|
Sign up to set email alerts
|

New Donor–Acceptor–Donor Conjugated Polymer with Twisted Donor–Acceptor Configuration for High-Capacitance Electrochromic Supercapacitor Application

Abstract: A new donor−acceptor−donor monomer chalcogena-diazolobenzotriazole (CDB)−3,4-ethylenedioxythiophene (EDOT) is designed and synthesized with a torsion angle of 39°b etween the donor EDOT and acceptor CDB due to the existence of large steric hindrance between the EDOT and planar CDB structures. The corresponding conjugated polymer film pCDB− EDOT is prepared via electrochemical deposition on indium tin oxide-coated glass, and their electrochromic and capacitive properties are characterized. The polymer film disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Then the device pCZ‐FSQ//ITO was assembled according to the previous method using ITO blank glass as the counter electrode and PMMA:LiBF 4 :[BMIM]BF 4 with a mixing ratio of 1:0.15:0.5 as the gel electrolyte. [ 2 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the device pCZ‐FSQ//ITO was assembled according to the previous method using ITO blank glass as the counter electrode and PMMA:LiBF 4 :[BMIM]BF 4 with a mixing ratio of 1:0.15:0.5 as the gel electrolyte. [ 2 ]…”
Section: Methodsmentioning
confidence: 99%
“…Electrochromism is the phenomenon of reversible color change in the appearance of a material under the action of an applied voltage. [1][2][3] Electrochromic materials are widely used in many fields such as aircraft portholes, electronic paper, glass curtain walls, etc., and have great development prospects. [4] The currently used organic electrochromic materials can be divided into organic small molecules and conductive polymers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to avoid strong charge localization leading to instability, a narrow band gap polymer composed of a cyclopentadithiophene donor and a proquinoidal thiophene-substituted thiadiazoloquinoxaline acceptor promoted extensive delocalization and stabilized unpaired spins in the backbone, demonstrating better performance than the other donor–acceptor polymers with a instability n-type moiety . However, the conjugated donor–acceptor ambipolar materials with extension of π-conjugation are not perfect for electrochromic supercapacitors because the color generally displayed in both the neutral state and doped state, which leads to difficulty in distinguishing the charging/discharging state. It is much easier for users to distinguish the change from transparent to colored due to the higher optical contrast. Therefore, connecting two redox-active π molecules showing transparency in the neutral state by nonconjugated alkyl chains not only separates the p-type and n-type materials but also prevents the color from being displayed in the neutral state and achieves a transparent-to-color electrochromic supercapacitor.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal oxides (such as WO 3 and NiO) possess stable and reversible redox reactions, and they have been used as active materials for electrochromic supercapacitors. But, researchers found that these oxides have some disadvantages in electrochromic performance like single color change, long response time, and coloration inefficiency, which limits their application in an electrochromic-supercapacitor difunctional device to some degree. Comparatively, conducting polymers (CPs) have unique advantages, such as good conductivity, good energy storage capacity, large voltage window, and multicolor, which are considered as an attractive option for electrochromic supercapacitors. , Among various CPs, polythiophene has higher conjugated electron cloud density than polypyrrole and polyaniline, which displays superior electrochemical performance. , Especially, when introducing ethylenedioxy, poly­(3,4-ethylenedioxythiophene) (PEDOT) possesses higher conductivity, lower oxidation potential, lower band gap, and better environmental stability, due to the outstanding electrochemical performance of CPs. , However, PEDOT and their derivatives often suffer from poor stability because the charge–discharge process and the overoxidation degradation can cause swelling and shrinking, which limits their application in some degree. According to the literature, this is mainly that the inner of polymers is not fully used. It is an effective method to obtain the desired polymer microstructure by changing the molecular structure because the molecular twist is usually changed by introducing side chains or complexing with other materials.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Especially, when introducing ethylenedioxy, poly(3,4-ethylenedioxythiophene) (PEDOT) possesses higher conductivity, lower oxidation potential, lower band gap, and better environmental stability, due to the outstanding electrochemical performance of CPs. 15,16 However, PEDOT and their derivatives often suffer from poor stability because the charge−discharge process and the overoxidation degradation can cause swelling and shrinking, which limits their application in some degree. According to the literature, this is mainly that the inner of polymers is not fully used.…”
Section: Introductionmentioning
confidence: 99%